Critical Analysis of Gurvadi Guna According to Hemadri- A Review Article. - Gangwar, Akanksha; Yadav, S S (International Research Journal of Ayurveda & Yoga, 2023)
Introduction-The ancient philosophy of well-being and healing called Ayurveda is the ‘Science of Life’, which has its roots back to the civilizations. The gurvadi guna help us to put words to what we sense and feel. They are 10 pairs of opposite gunas. For example- heavy-light (guru-laghu), cold-hot (shita-ushna), unctous-dry (snigdha-ruksha), etc. Some of them make perfect sense in modern medicine too, as hot for fever or cracking skin would be dry etc. The same concept can be used to find any balance in life. Materials and Methods- Among all the samhitas of Ayurveda, the Acarya Hemadri in his commentary, Ayurveda rasayana on Ashtang Hridaya; have done the detailed analysis about gurvadi guna, which no one else has done. These attributes can be seen as energies or forces in our environment and within us. Results- The exact estimation of predominance of guna leading to vitiation of doshas helps us to understand the pathogenesis and treatment can be planned with the help of opposite guna. The detailed discussion about each and every guna helps to develop a better understanding and clarification of the concept. Conclusion- It is important to estimate the hetus of every individual and estimate the guna predominance out of it which leads to vitiation of doshas and generation of disease for proper diagnosis and effective treatment. Appropriate knowledge of guna may help the practitioner to understand the disease along with that the drugs used for the treatment would be well understood at every minute level and prescribed.